Response of some Rapeseed (Brassica napus L.) varieties to Zn fertilizer Under Dryfarming Conditions - Abdulkhaleq, Dana Azad; Hama, Shara Jalal; Ahmad, Rozhgar Mustafa; Tawfiq, Sherwan Ismael (Sulaimani Journal for Pure and Applied Sciences, 2018)
This investigation was conducted during the winter seasons of 2016-2017 at The Qlyasan Agricultural Research Station, College of Agricultural Sciences, University of SuLAmani, using split plot design the main plots conducted in Randomized Complete Block Design (RCBD) with three replicates to study the effect of three levels of zinc fertilizer on the growth, yield and yield component of rapeseed varieties. The three varieties; Serw, Hybrid and Reandy were implemented in the main plots, three zinc fertilizer levels (0, 20 and 40) kg Zn/ha from ZnSO4 source, were implemented in the subplot. Comparisons between means were carried out by the leaset significant difference (L.S.D) at 1 % and 5 % level of significance. The results of this investigation confirm that variety Reandy produced the best values for most characters, and the application 40Kg Zn/ha was found to be the best level for this crop. The character seed yield showed positive and highly significant correlation with most characters including plant height, number of leaves per plant, number of pods per plant, the weight of pod per plant, average pod weight, 1000-seed weight, dry matter weight per plant and biological yield. The maximum positive direct effect on seed yield recorded by an average pod weigh with 0.898, while the maximum positive indirect effect on seed yield recorded by biological yield via average pod weight with 0.840.
Keywords: Rapeseed varieties; Zn Foliar Application; Growth; Yield and yield component; Oil percentage; Correlation and Path Analysis